2022
DOI: 10.1093/sleep/zsac107
|View full text |Cite
|
Sign up to set email alerts
|

Risk of COPD exacerbation is increased by poor sleep quality and modified by social adversity

Abstract: Study Objectives Sleep is an important dimension in the care of chronic obstructive pulmonary disease (COPD), but its relevance to exacerbations is unclear. We wanted to assess whether sleep quality as measured by the Pittsburgh Sleep Quality Index (PSQI) is associated with an increased risk of COPD exacerbations and does this differ by socio-environmental exposures. Methods We included 1647 current and former smokers with sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…Sleep disturbances are prevalent in these patients and have been found to be associated with unfavorable clinical outcomes and reduced quality of life [ 14 ]. The results of our study indicated a high prevalence of poor sleep quality (69%) and symptoms of insomnia (75.5%), mirroring findings from prior studies [ 9 , 13 , 111 , 112 , 113 , 114 ]. Our study also revealed a higher prevalence of poor sleep quality and insomnia symptoms in patients with lower social support.…”
Section: Discussionsupporting
confidence: 88%
“…Sleep disturbances are prevalent in these patients and have been found to be associated with unfavorable clinical outcomes and reduced quality of life [ 14 ]. The results of our study indicated a high prevalence of poor sleep quality (69%) and symptoms of insomnia (75.5%), mirroring findings from prior studies [ 9 , 13 , 111 , 112 , 113 , 114 ]. Our study also revealed a higher prevalence of poor sleep quality and insomnia symptoms in patients with lower social support.…”
Section: Discussionsupporting
confidence: 88%
“…[23] Although studies assessing the temporality between COPD and NSW are lacking, the detrimental effects of sleep deprivation on COPD are well documented. [61][62][63] Sleep-deprived adults were associated with almost a 5-fold higher chance of COPD exacerbation and more than 11-fold emergency visits for respiratory-related complaints. Additional evidence suggests that insomnia predicted COPD exacerbations and worse survival during follow-ups.…”
Section: Night Shift Work Associated With Copdmentioning
confidence: 99%
“…An extensive search of the existing literature yielded no studies describing CLIs for the prevention of the onset of asthma or COPD. The primary focus of the CLIs was on secondary and tertiary prevention, even though the existing literature suggests an optimal lifestyle not only slows lung function decline in patients but can also play a role in reducing asthma and COPD risk [13][14][15][16][17][18][19][20][21][22][23]. As this review showed that CLIs are effective in asthma and COPD management, one could question whether the implementation of CLIs would not already be beneficial at an earlier stage.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, excessive alcohol use has been associated with pulmonary function decline and increased risk of asthma [17,19]. Furthermore, psychological stress and poor sleep quality have been associated with worse outcomes in asthma and COPD [20][21][22][23], making them important targets for intervention.…”
Section: Introductionmentioning
confidence: 99%